Selenium and Polycystic Ovary Syndrome; Current Knowledge and Future Directions: A Systematic Review - Hajizadeh-Sharafabad, Fatemeh; Moludi, Jalal; Tutunchi, Helda; Taheri, Ehsaneh; Izadi, Azimeh; Maleki, Vahid (Hormone and Metabolic Research, 2019)
Polycystic ovary syndrome (PCOS), as the most common endocrine disorder in reproductive-aged women, is recognized by hyperandrogenism and insulin resistance. Selenium (Se) potentially possesses therapeutic effects on PCOS due to antioxidant and insulin-like properties. This systematic review evaluates the potential role of Se in the complications of PCOS. A systematic review was performed on published studies reporting the effects of Se on PCOS. Three major databases including PubMed, Scopus, and Google Scholar were searched until December 2018. A total of 7 human studies and two in vitro studies met the inclusion criteria. Two out of three case-control studies showed that serum Se levels tend to decrease in patients with PCOS. Of four studies that evaluated the impact of Se supplementation on insulin resistance, only one study showed protective effects of Se against insulin resistance. Two out of three studies reported the antioxidant effect of Se. Few studies investigating anti-androgenic effect of Se presented controversial results. There were three studies that evaluated the anti-hyperlipidemic effect of Se, of which two surveys indicated the lowering effects of Se on VLDL and LDL-cholesterol. The reviewed studies confirmed inverse relationships between serum Se levels and some androgenic hormones in PCOS. Se is able to attenuate insulin resistance and dyslipidemia. The available data are currently insufficient to support the protective effects of Se on PCOS.
Keywords: selenium; PCOS; insulin resistance; dyslipidemia